EFFECT OF PROPELLER POSITIONS ON THE MODELS OF DELTA-WINGED UAV - Khushairi Amri Kasim, 1991-, author 634397; Shabudin Mat, author 618557; Yahaya Ramli, author 608286; Iskandar Shah Ishak, 1973-, author 521953 (Johor Bahru, Johor: PENERBIT UTM PRESS, 2023)
Includes bibliographical references and index.